Blockade of ErbB2 and PD-L1 using a bispecific antibody to improve targeted anti-ErbB2 therapy. (2nd November 2019) - Mittal, Deepak; Vijayan, Dipti; Neijssen, Joost; Kreijtz, Joost; Habraken, Maurice M. J. M.; Van Eenennaam, Hans; Van Elsas, Andrea; Smyth, Mark J.
ABSTRACT: A significant proportion of human epidermal growth factor receptor 2 (Her2/ErbB2)-positive metastatic breast cancer patients are refractory to Her2-targeted trastuzumab-like therapy. Some of this resistance has been attributed to the upregulation of immune checkpoints such as programmed cell death-1 (PD-1) and its ligand, PD-L1 in Her2-positive breast cancer patients. Therefore, therapies targeting both the PD-1/PD-L1 interaction and oncogenic Her2 signaling are of significant clinical interest. Here, we constructed a mouse bispecific antibody targeting PD-L1 and rat Her2 (referred to as BsPD-L1xrErbB2) aiming to redirect the anti-PD-L1 response toward Her2-expressing tumor cells. BsPD-L1xrErbB2 demonstrated additive binding to interferon (IFN)-γ treated Her2 + TUBO tumor cells, but it did not affect the proliferation of tumor cells in-vitro . BsPD-L1xrErbB2 also blocked the PD-1/PD-L1 interaction. This bispecific antibody was constructed with a mouse IgG2a Fc backbone and interacted with Fcγ receptors and resulted in complement deposition (C3). ADCC and complement action could be potential mechanisms of action of this molecule. BsPD-L1xrErbB2 successfully reduced TUBO tumor growth and increased tumor rejection rate compared to the monovalent anti-PD-L1, monovalent anti-ErbB2 or the combination of anti-PD-L1 and anti-ErbB2 monotherapies. The enhanced anti-tumor effect of BsPD-L1xrErbB2 was dependent on CD8 + T lymphocytes and IFN-γ, as depletion of CD8 + T lymphocytes and neutralization of IFN-γ completely abolished the antitumor activity of the bispecific antibody. Consistently, BsPD-L1xrErbB2 treatment also increased the frequency of intratumor CD8 + T lymphocytes. Taken together, our data support a bispecific antibody approach to enhance the anti-tumor efficacy of PD-1/PD-L1 checkpoint blockade in Her2-positive metastatic breast cancers.